(untitled) - Food & Agriculture Organization of the United Nations (FAO) (Bangkok, 1996)
This document reports the outcome of the Workshop aimed to build a common understanding among the key participants from the Department of Fisheries of Thailand, the fishers and village leaders, universities and NGOs, of the importance benefits and constraints, roles and responsibilities,...
Keywords: Fishery management,Quản lý nghề cá; Thailand,Thái Lan